Ijtihad Imam Ahmad bin Hanbal dan Implementasinya dalam Keuangan Syariah: Analisis Kuantitatif Pembiayaan dan Non Performing Financing (NPF) di Indonesia 2019–2024 - Nopitasari, Vialdi; Muhajirin, Muhajirin (Universitas Batanghari Jambi, 2025)
This study aims to examine the relevance of Imam Ahmad bin Hanbal's ijtihad principles, particularly the emphasis on the use of text-based contracts, in the context of modern Islamic finance in Indonesia. The research method used is a quantitative approach with time series data for the period 2019–2024. The variables used include murabahah; ijarah; total weak hadith; and sukuk as independent variables and non-performing financing as the dependent variable. The analytical tool used is multiple linear regression. The results show that murabahah has a negative and significant effect on non-performing financing (NPF), while ijarah, total weak hadith, and sukuk are not significant. Simultaneously, this research model is almost significant with a high coefficient of determination (R²), this confirms that Imam Ahmad bin Hanbal's ijtihad principles that prioritize texts are still relevant in contemporary Islamic financial practices, especially in maintaining financing quality.